On the Methodologies of Private International Law: A Contribution to Their Study within the Framework of the Uruguayan Legal System - Ferreira Marino , Alejandro Matías; Pereira Fantoni , Verónica (Revista de Derecho, 2025)
The various multinational situations, i.e., those private relationships with foreign elements susceptible to regulation by Private International Law, can be dealt with by means of different techniques and methods, according to the fair solutions that the legislator considers appropriate for each particular case. In our discipline, this issue is known as “the question of methods”. The present research aims to carry out a detailed analysis of the three main methods of resolution in the field of Private International Law, with a special focus on the Uruguayan legal framework. In Uruguay, most of the provisions follow the conflict method in its bilateral form, as established in the Montevideo treaties of 1889 and 1940 and in various inter-American conventions. However, with the enactment of Law 19.920, a significant methodological renewal is introduced in the treatment of multinational cases, incorporating rules of immediate or necessary application and adopting unilateral criteria. Thus, a study of the question of methods in the light of this new regulation, which represents an advance in the Uruguayan approach to international private relations, is indispensable.